DRIVERS OF CUSTOMER SATISFACTION IN ISLAMIC MOBILE BANKING: AN ANALYSIS OF SERVICE QUALITY, EASE OF USE, TRUST, AND ISLAMIC MARKETING ETHICS IN INDONESIA - Tripuspitorini, Fifi Afiyanti; Rahmawati, Dina Alya; Ibtisamah, Rana (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2025)
The rapid evolution of digital technology has transformed banking services, with Islamic banks leveraging mobile banking innovations to meet customer needs while adhering to sharia principles. This study investigates the influence of service quality, ease of use, trust, and Islamic marketing ethics on customer satisfaction among mobile banking users in Islamic banks in Indonesia. Employing a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), data were collected from 55 Islamic bank mobile banking users via an online questionnaire. The measurement model confirmed the validity and reliability of all indicators, with discriminant validity established through the Fornell-Larcker criterion. The structural model revealed that the variables collectively explain 70.1% of the variance in customer satisfaction, with a Goodness of Fit (GoF) value of 0.722 indicating a robust model fit. Hypothesis testing demonstrated that ease of use and trust significantly and positively influence customer satisfaction, whereas service quality and Islamic marketing ethics showed no significant effect. These findings suggest that Islamic banks should prioritize user-friendly mobile banking interfaces and foster trust through secure systems and sharia compliance to enhance customer satisfaction. This study offers valuable insights for Islamic banks aiming to align technological advancements with ethical principles to elevate customer experiences.